CD56bright natural killer cells preferentially kill proliferating CD4+ T cells - Lee, M; Bell, CJM; Rubio Garcia, A; Godfrey, L; Pekalski, M; Wicker, LS; Todd, JA; Ferreira, RC (Oxford University Press, 2023)
Human CD56br natural killer (NK) cells represent a small subset of CD56+ NK cells in circulation and are largely tissue-resident. The frequency and number of CD56br NK cells in blood has been shown to increase following administration of low-dose IL-2 (LD-IL2), a therapy aimed to specifically expand CD4+ regulatory T cells (Tregs). Given the potential clinical application of LD-IL-2 immunotherapy across several immune diseases, including the autoimmune disease type 1 diabetes, a better understanding of the functional consequences of this expansion is urgently needed. In this study, we developed an in vitro co-culture assay with activated CD4+ T cells to measure NK cell killing efficiency. We show that CD56br and CD56dim NK cells show similar efficiency at killing activated CD4+ conventional T (Tconv) and Treg cell subsets. However, in contrast to CD56dim cells, CD56br NK cells preferentially target highly proliferative cells. We hypothesize that CD56br NK cells have an immunoregulatory role through the elimination of proliferating autoreactive CD4+ Tconv cells that have escaped Treg suppression. These results have implications for the interpretation of current and future trials of LD-IL-2 by providing evidence for a new, possibly beneficial immunomodulatory mechanism of LD-IL-2-expanded CD56br NK cells.